PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN NILAI PERUSAHAAN TERHADAP TAX AVOIDANCE KASUS PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Nawang Kalbuana (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This study aims to determine the Company Size, Leverage, Company Value on Tax Avoidance: The Case of Companies Listed in the Jakarta Islamic Index (JII). The approach used in this research is a quantitative approach. The data in this study are secondary data. Data obtained from the page www.idnfinancial.com. Sampling technique using purposive sampling technique and data analysis using multiple linear regression analysis. The findings show that Company Size and Firm Value do not affect Tax Avoidance while Leverage has a significant effect on Tax Avoidance